Enhanced photocontrolled binding of Ag+ by thioindigo derivative containing oxyethylene chains with OH groups at the terminal positions - Rahman, Shah Mohammad Fatah-Ur; Shahjin, Farah; Fukunishi, Koushi (Journal of Bangladesh Academy of Sciences, 2014)
A novel thioindigo dye was synthesized, from 7, 7-bis-chlorocarbonyl thioindigo, containing OH groups at the terminal positions of the oxyethylene side chains. The resultant dye 7, 7-Bis[[2- [2-(2-hydroxyethoxy)ethoxy]ethoxycarbonyl]thioindigo (1) was characterized by 1H NMR, IR, and mass spectral studies. The thioindigo derivative (1), which possesses a molecular architecture, undergoes reversible photochromic reaction and capable of capturing different metal ions and transports them through liquid membrane. Enhancement of binding ability (i) by incorporating OH groups instead of large phenyl or methyl groups, (ii) by trans to cis photoisomerization of (1), iii) the highest amount of transported Ag+ by (1) across a liquid membrane when irradiated with 550 and 480 nm light alternately, were found. DOI: http://dx.doi.org/10.3329/jbas.v37i2.17564 Journal of Bangladesh Academy of Scinces, Vol. 37, No. 2, 219-229, 2013